UKINUĆE ČOVJEKA - Lewis, C. S.; Abadžić-Hodžić, Aida (Novi Muallim, 2006)
Iz: C.S.Lewis, The Abolition of Man, New York, The Macmilian Company, 1947. Za naš prijevod preuzeto iz: Philosophy and Technology,Readings in the Philosophical Problems of Technology, Edited with an Introduction by: Carl Mitcham and Robert Mackey, The Free Press, N.Y., 1983, p. 143- 150. Prijevbod s engleskog: Aida Abadžić-Hodžić